2005
DOI: 10.1139/x05-036
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific divergence in foliar nutrient dynamics and stem growth in a temperate forest in response to chronic nitrogen inputs

Abstract: Abstract:We studied the effects of excessive nitrogen (N) fertilization on foliar nutrient dynamics and stem growth in three important tree species in a mixed-deciduous forest. Stem diameter growth, foliar N concentrations, nitrogenphosphorus (N/P) ratios, and nutrient resorption were determined for Acer rubrum L. (ACRU), Liriodendron tulipifera L. (LITU), and Prunus serotina Ehrh. (PRSE) on two 30-year-old watersheds at the Fernow Experimental Forest, West Virginia, USA: WS3, fertilized annually with 35 kg am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 34 publications
2
32
2
Order By: Relevance
“…Boxman et al (1998) also found that reducing N deposition in throughfall on roofed plots at Ysselsteyn, Netherlands resulted in significantly improved radial growth of Scots pine, suggesting that growth was being suppressed by ambient throughfall. Finally, May et al (2005) also noted reduced diameter growth in black cherry, yellow-poplar, and red maple trees at Fernow from 1999 to 2001, during the period of decline in growth noted by the tree cores. Theories of forest ecosystem acidification discussed in Chapter 1 suggest that a pattern of increased followed by decreased growth can result from prolonged exposure to acidic deposition.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Boxman et al (1998) also found that reducing N deposition in throughfall on roofed plots at Ysselsteyn, Netherlands resulted in significantly improved radial growth of Scots pine, suggesting that growth was being suppressed by ambient throughfall. Finally, May et al (2005) also noted reduced diameter growth in black cherry, yellow-poplar, and red maple trees at Fernow from 1999 to 2001, during the period of decline in growth noted by the tree cores. Theories of forest ecosystem acidification discussed in Chapter 1 suggest that a pattern of increased followed by decreased growth can result from prolonged exposure to acidic deposition.…”
Section: Discussionmentioning
confidence: 73%
“…As indicated in Figure 5-9 increases were significant in yellow-poplar during 3 years and in black cherry during 7 years prior to 1996. May et al (2005) found diameter growth on WS3 reduced by 37% compared to WS7 from 1999-2001 in three each of red maple, yellow-poplar, and black cherry trees. These data were collected late in the treatment period analyzed here and support the tree core analysis showing reduced radial growth had occurred.…”
mentioning
confidence: 83%
“…Differences in foliar nutrient concentrations were observed , May et al 2005, which suggests there may have been differences in N uptake by the vegetation. Specifically, N concentrations of foliage collected in 1992 from WS3 were generally higher than from WS7 for four tree species: red maple, black cherry, yellow-poplar, and sweet birch -but were only significantly greater on WS3 relative to WS7 for black cherry and red maple.…”
Section: Internal Cyclingmentioning
confidence: 92%
“…May et al (2005) reported that the acidification treatment decreased nutrient resorption efficiencies on WS3. The resorption of N averaged 30% lower in WS3 for red maple and black cherry than in WS7, but there were no significant differences in N resorption efficiency between watersheds for yellow-poplar.…”
Section: Internal Cyclingmentioning
confidence: 99%
See 1 more Smart Citation